Testicular microlithiasis defines a subgroup of azoospermic men with low rates of sperm retrieval. (4th October 2021) - Barda, Shimi; Hauser, Ron; Mano, Roy; Savin, Ziv; Molad‐Hayo, Yonatan; Lehavi, Ofer; Kleiman, Sandra E; Azem, Foad; Yossepowitch, Ofer; Dekalo, Snir
Abstract : Objective: To investigate the prevalence of testicular microlithiasis and its association with sperm retrieval rates and histopathology in men with non‐obstructive azoospermia. Methods: A total of 120 men underwent scrotal ultrasonography prior to microsurgical testicular sperm extraction. Sperm retrieval rate, testicular histopathology, testicular size, reproductive hormones, karyotyping, Y chromosome microdeletion analyses, and presence of varicoceles and hydroceles were compared between men with and without testicular microlithiasis. Results: The total sperm retrieval rate was 40%. Ten men with normal spermatogenesis were excluded. The remaining 110 men with non‐obstructive azoospermia were analyzed and testicular microlithiasis was detected in 16 of them (14.5%). The sperm retrieval rate in that subgroup was only 6.2% (1/16) as opposed to 39.4% (37/94) in men with non‐obstructive azoospermia and no evidence of microlithiasis ( P  = 0.009). The mean right and left testicular diameters were significantly lower in the microlithiasis group ( P  = 0.04). On multivariate logistic regression analysis, the presence of mictolithiasis (odds ratio 7.4, 95% confidence interval 2.3, 12.2; P  = 0.01) was the only independent predictor of unsuccessful sperm retrieval. The 15 patients with microlithiasis and without successful sperm extraction were diagnosed by histopathology as having Sertoli cells only. The 16th patient with successful sperm retrieval had a histopathology of mixed atrophy and was diagnosed with Klinefelter syndrome. Conclusion: The presence of testicular microlithiasis is associated with low sperm retrieval rates among our cohort of men with non‐obstructive azoospermia undergoing scrotal ultrasonography prior to microsurgical testicular sperm extraction. Larger, prospective studies should be conducted to confirm these findings.